A Novel Phenotype of Nonsteroidal Anti-Inflammatory Drug Hypersensitivity - Mario Sánchez-Borges (World Allergy Organization Journal, 2009)
Background Some nonsteroidal anti-inflammatory drug (NSAID)-hypersensitive patients develop adverse reactions when challenged with weak cyclooxygenase 1 (COX-1) inhibitors.Objectives To investigate the prevalence and clinical features of this high-risk population.Materials and methods Patients from 2 outpatient allergy clinics consulting between October 2005 and October 2007 because of adverse reactions to classic NSAIDs were submitted to confirmatory double-blind oral challenges with the suspected NSAID and with acetaminophen, preferential and/or specific COX-2 inhibitors. Patients were then classified as low-risk and high-risk groups according to the results of provocation tests.Results Three hundred three patients were studied: 179 (59.0%) were tolerant to acetaminophen and the selective COX-2 inhibitors (low-risk group), whereas 124 (40.9%) developed reactions to at least one of the ''low COX-1 inhibitors'' (high-risk group). No distinctive demographic or clinical characteristics were present when both groups of patients were compared.Conclusions A large proportion of patients sensitive to classic NSAIDs cannot tolerate the weak COX-1 inhibitors. Oral challenges should be performed by trained specialists to advise these patients about the use of NSAIDs. Keywords: aspirin, angioedema, cyclooxygenases, NSAIDs, urticaria